2013
DOI: 10.1111/sae.12007
|View full text |Cite
|
Sign up to set email alerts
|

Blood Loss and the Need for Transfusion after Shoulder Surface Replacement

Abstract: Background Studies on stemmed primary shoulder arthroplasty have shown transfusion rates of up to 38%. The present study aimed to evaluate blood loss and the need for blood transfusion after primary humeral and total shoulder surface replacement. Materials and methods Patients undergoing both primary humeral head (n = 20) and total shoulder (n = 63) resurfacing were included. The mean drop in haemoglobin levels on the first postoperative day and the need for transfusion were recorded and analyzed against the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Other recent studies on primary total SA and shoulder surface replacement have also reported transfusion rates lower than 4%. 39,40 As a result, the effectiveness and cost-effectiveness of TXA in terms of decreasing the need of transfusions would be marginal in this specific subgroup of patients, as it would be required to treat a very high number of patients with TXA for preventing only one event of transfusion. These conclusions may not apply to patients with a higher baseline risk of transfusion such as revision arthroplasty, arthroplasty for fractures or patients with preoperative anemia, in whom TXA may be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies on primary total SA and shoulder surface replacement have also reported transfusion rates lower than 4%. 39,40 As a result, the effectiveness and cost-effectiveness of TXA in terms of decreasing the need of transfusions would be marginal in this specific subgroup of patients, as it would be required to treat a very high number of patients with TXA for preventing only one event of transfusion. These conclusions may not apply to patients with a higher baseline risk of transfusion such as revision arthroplasty, arthroplasty for fractures or patients with preoperative anemia, in whom TXA may be more effective.…”
Section: Discussionmentioning
confidence: 99%